2020
DOI: 10.1128/aac.00924-20
|View full text |Cite
|
Sign up to set email alerts
|

Screening Repurposing Libraries for Identification of Drugs with Novel Antifungal Activity

Abstract: Fungal organisms are ubiquitous in nature, and progress of modern medicine is creating an expanding number of severely compromised patients susceptible to a variety of opportunistic fungal infections. These infections are difficult to diagnose and treat, leading to high mortality rates. The limited antifungal arsenal, the toxicity of current antifungal drugs, the development of resistance, and the emergence of new multidrug resistant fungi, all highlight the urgent need for new antifungal agents. Unfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 71 publications
0
39
0
Order By: Relevance
“…Recently, a number of papers have been published that examine different aspects of PAS on P. aeruginosa biofilms [ 16 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. We were particularly interested to discover whether pragmatic PAS with a lytic phage and AzLys was more effective at eradicating PA01 biofilms than phage treatment alone.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a number of papers have been published that examine different aspects of PAS on P. aeruginosa biofilms [ 16 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. We were particularly interested to discover whether pragmatic PAS with a lytic phage and AzLys was more effective at eradicating PA01 biofilms than phage treatment alone.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, re-colonization is common due to P. aeruginosa persistence in the upper airways [ 66 ]. However, PAS has the potential to improve treatment for chronic infections with the combined action of antibiotics and select phages increasing killing activity against pathogens [ 13 , 14 , 16 , 36 , 37 , 41 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ], and a variety of studies have shown that the combined use of antibiotics and phages reduces the emergence of resistance to one or both killing agents [ 16 , 68 , 69 , 70 , 74 , 75 , 76 , 77 ]. In this study, we show that AzLys is able to increase the activity of phages E79 and phiKZ.…”
Section: Discussionmentioning
confidence: 99%
“… 62 In a Galleria mellonella infection model, co-incubation of monophage Sb-1 and PYO bacteriophage, two commercially available phage formulations, eradicated MRSA biofilm and prevented biofilm formation by completely abolishing heat production of MRSA. 63 Unlike mono phage applications which are mostly lytic phages, phage cocktail could be a mixture of only lytic phages, temperate phages or both. Four temperate phages Trsa205, Trsa207, Trsa220 and Trsa222 in a cocktail, was capable of removing 65% of S. aureus biofilms, in addition to lysing two-thirds of the isolates.…”
Section: Application Of Phages In Bacterial Biofilm Destructionmentioning
confidence: 99%
“…These efforts can be facilitated by screening repurposing libraries with high representation of FDA-approved compounds. Indeed, in the last few years there has been an increasing interest by different academic groups in the screening of such libraries in search for drugs with novel antifungal activity (recently reviewed in (Wall and Lopez-Ribot, 2020b). In the case of C. auris, there is only a limited number of reports regarding the implementation of this approach (Wall et al, 2018;de Oliveira et al, 2019;Wall et al, 2019).…”
Section: Discussionmentioning
confidence: 99%